2022
DOI: 10.3389/fphar.2022.983623
|View full text |Cite
|
Sign up to set email alerts
|

Iron dyshomeostasis and ferroptosis in Alzheimer’s disease: Molecular mechanisms of cell death and novel therapeutic drugs and targets for AD

Abstract: Alzheimer’s disease (AD) is a degenerative disease of the central nervous system that is the most common type of senile dementia. Ferroptosis is a new type of iron-dependent programmed cell death identified in recent years that is different from other cell death forms. Ferroptosis is induced by excessive accumulation of lipid peroxides and reactive oxygen species (ROS) in cells. In recent years, it has been found that ferroptosis plays an important role in the pathological process of AD. Iron dyshomeostasis co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 115 publications
0
19
0
Order By: Relevance
“…20,21 Patients with mild cognitive impairment (MCI) and high amyloid plaque loads exhibit an increase in cortical iron accumulation, which heightens the risk of AD. 22 Ferroptosis, a form of regulated cell death, has been implicated in the development of AD, characterized by iron-driven lipid peroxidation and glutamate excitotoxicity in the brain tissues of AD patients and models. Cerebrospinal fluid (CSF) ferritin levels have been found to be inversely associated with MCI and AD, with the Alzheimer's risk allele APOE-ε4 increasing ferritin levels, indicating that iron imbalance may be a risk factor for AD.…”
Section: Introductionmentioning
confidence: 99%
“…20,21 Patients with mild cognitive impairment (MCI) and high amyloid plaque loads exhibit an increase in cortical iron accumulation, which heightens the risk of AD. 22 Ferroptosis, a form of regulated cell death, has been implicated in the development of AD, characterized by iron-driven lipid peroxidation and glutamate excitotoxicity in the brain tissues of AD patients and models. Cerebrospinal fluid (CSF) ferritin levels have been found to be inversely associated with MCI and AD, with the Alzheimer's risk allele APOE-ε4 increasing ferritin levels, indicating that iron imbalance may be a risk factor for AD.…”
Section: Introductionmentioning
confidence: 99%
“…These soluble Aβ oligomers can disrupt synaptic function and impair neurotransmission, leading to synaptic dysfunction and ultimately synapse loss. Moreover, increasing evidence suggests a connection between dysregulated brain iron and the progression of AD, and this dysregulation has been implicated in the mechanism of neurodegeneration known as ferroptosis 30,31 . Our results of the role of BA and betaine in synaptosomes treated with Aβ (1–42) has been expanded by biochemical analyses demonstrating that disruptions in synaptosomes function, either through lipid or DNA damages, make synaptosomes more susceptible to ferroptosis.…”
Section: Discussionmentioning
confidence: 55%
“…Moreover, increasing evidence suggests a connection between dysregulated brain iron and the progression of AD, and this dysregulation has been implicated in the mechanism of neurodegeneration known as ferroptosis. 30,31 Our results of the role of BA and betaine in synaptosomes treated with Aβ (1-42) has been expanded by biochemical analyses demonstrating that disruptions in synaptosomes function, either through lipid or DNA damages, make synaptosomes more susceptible to ferroptosis. For the first time in this study, we found that BA and betaine pre-treatment did not cause any morphological and biochemical changes in rat brain tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Iron is a trace metal essential to the human body and is essential for normal cell function. The main storage form of iron in cells is ferritin, when intracellular iron deficiency or iron demand increases, ferritin released through selective autophagy to provide bioavailable iron to maintain intracellular iron homeostasis (Masaldan et al, 2018; Tang et al, 2019; Y. Zhang, Wang, & Chang, 2022). Accumulating studies found that NCOA4 knockdown inhibited ferritin degradation, reduced iron accumulation and intracellular ROS in cancer cells and fibroblasts, and thus inhibited ferroptosis, whereas NCOA4 overexpression has the opposite effect (J. Liu, Zhang, et al, 2022; Mancias et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Iron is a trace metal essential to the human body and is essential for normal cell function. The main storage form of iron in cells is ferritin, when intracellular iron deficiency or iron demand increases, ferritin released through selective autophagy to provide bioavailable iron to maintain intracellular iron homeostasis (Masaldan et al, 2018;Tang et al, 2019;Y. Zhang, Wang, & Chang, 2022).…”
mentioning
confidence: 99%